From ‘Christification’ to Mission of Salvation: Impact of Damascus Event on Saint Paul - Hidayat, Elvin Atmaja (Faculty of Philosophy, Parahyangan Catholic University, Bandung, 2021)
Saint Paul is one of the most important apostles in Christianity. The mission of evangelism he carried out was fruitful in various parts of the world. Paul’s missionary journey brought great risks to himself through the challenges and the sufferings, while he was also previously known as a persecutor of Christ’s followers. His radical change or conversion occurred since his spiritual encounter with the Lord Jesus on his journey to Damascus. This article explores the impact of the unforgettable encounter that brings to Paul more admiration and love for Christ, that also brings an extraordinary mystical experience of ‘christification’, an experience of becoming more and more alike and united with the Christ. The Damascus event and the christification open the divine revelation of human salvation. As a Jew, Paul recognises that salvation is obtained by obeying the law, but now he believes that only the risen Jesus Christ is able to save humankind. Paul’s christification brings direct implications to his courage in becoming a follower of Christ with a burning passion to proclaim the Gospel to all nations. God’s choice for an apostle is unfathomable, even for Paul himself who considers himself as the most sinful and unworthy person.